Pengembangan Media Pembelajaran PAI Berbasis Lingkungan melalui Model ASSURE - Baharun, Hasan (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2016)
This paper presents the technique of instructional media development of Islamic Education using environment based with ASSURE models in order to make the instruction more efficient. Learning activity is basically a process of communication and interaction between learners and educators organized to achieve the objectives that have been planned. To create effective communication, it requires the development of instructional media - in addition to the other aspects - based environment through ASSURE models. This is conducted to set up learning conditions of Islamic education which lead classroom activities centered on students, empower their activeness, provide interests, avoid monotonous tasks and boredoms, as well as foster studentsâ enthusiasm to study harder. Environment based learning as part of contextual learning provides students direct experiences in interacting with the surrounding environment, such as social, natural and constructed environment, so as to create conditions that are more meaningful and enable them to build better personalities and characters, such as love of the environment.ØØ§ÙÙØª ÙØ°Ù Ø§ÙÙÙØ§ÙØ© Ø¹Ø±Ø¶ Ø¨Ø¹Ø¶ Ø§ÙØ£Ø³Ø§ÙÙØ¨ ÙØªØ·ÙÙØ± Ø§ÙÙØ³Ø§Ø¦Ù Ø§ÙØªØ¹ÙÙÙÙØ© ÙÙØ§Ø¯Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø¹ÙÙ Ø£Ø³Ø§Ø³ Ø§ÙØ¨ÙØ¦Ø© ÙÙÙÙÙ Ø§ÙØªØ¯Ø±ÙØ³ ÙØ¹ÙØ§ÙØ§ Ø¹ÙÙ ÙÙÙØ°Ø¬ ASSURE. ÙØ§ÙØªØ¹ÙÙÙ Ø£Ø³Ø§Ø³Ø§ ÙÙ Ø¹ÙÙÙØ© Ø§ÙØ§ØªØµØ§Ù Ø¨ÙÙ Ø§ÙÙØ¹ÙÙÙ ÙØ§ÙÙØªØ¹ÙÙÙ ÙÙÙØµÙÙ Ø¥ÙÙ Ø§ÙØ£ÙØ¯Ø§Ù Ø§ÙÙÙØ±ÙØ±Ø©. ÙÙØªÙÙÙÙ Ø¹ÙÙÙØ© Ø§ÙØ§ØªØµØ§Ù ÙØ¹ÙØ§ÙØ© ÙÙØØªØ§Ø¬ Ø¥ÙÙ ØªØ·ÙÙØ± Ø§ÙÙØ³Ø§Ø¦Ù Ø§ÙØªØ¹ÙÙÙÙØ© â ÙØºÙØ±ÙØ§ ÙØ°ÙÙ â Ø¹ÙÙ Ø£Ø³Ø§Ø³ Ø§ÙØ¨ÙØ¦Ø© ÙÙ ÙÙÙØ°Ø¬ ASSURE. ÙØ§ÙÙØ¯Ù ÙÙ ÙØ°Ø§ ØªÙÙÙÙ Ø¸Ø±ÙÙ ØªØ¹ÙÙÙ ÙØ§Ø¯Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙØªÙØ±ÙØ²Ø© ÙÙ Ø§ÙØ·ÙØ§Ø¨Ø ÙØªÙØ¹ÙÙ Ø§ÙØ·ÙØ§Ø¨ ÙØªÙÙÙÙÙÙØ ÙØ¥Ø²Ø§ÙØ© Ø§ÙØ±ØªÙØ¨ ÙØ§ÙØ³Ø¢ÙØ© ÙÙÙÙØ ÙØºØ±Ø³ Ø§ÙØÙØ§Ø³Ø© ÙØªÙÙÙØªÙØ§ ÙÙ Ø§ÙØªØ¹ÙÙÙ. ÙØ§ÙØªØ¹ÙÙÙ Ø¹ÙÙ Ø£Ø³Ø§Ø³ Ø§ÙØ¨ÙØ¦Ø© ÙÙØ¹ ÙÙ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ³ÙØ§ÙÙØ ÙØ¹Ø·Ù Ø§ÙØ·ÙØ§Ø¨ Ø§ÙÙØ§ÙØ¹ Ø§ÙØ¹ÙÙÙ ÙÙ Ø§ÙØªØ¹Ø§ÙÙ ÙØ¹ Ø¹Ø¯Ø© Ø§ÙØ¨ÙØ¦Ø§Øª Ø§ÙÙØÙØ·Ø© Ø¨ÙÙØ Ø§ÙØ¨ÙØ¦Ø© Ø§ÙØ§Ø¬ØªÙØ§Ø¹ÙØ©Ø ÙØ§ÙØ¨ÙØ¦Ø© Ø§ÙØ·Ø¨ÙØ¹ÙØ©Ø ÙØ§ÙØ¨ÙØ¦Ø© Ø§ÙØ§ØµØ·ÙØ§Ø¹ÙØ© ØØªÙ ÙÙØ¯Ø±ÙØ§ Ø¹ÙÙ ØªÙÙÙÙ Ø¸Ø±ÙÙ Ø§ÙØªØ¹ÙÙÙ Ø°Ø§Øª ÙØ¹ÙÙ ÙÙÙ ØØªÙÙ ØªÙÙÙÙØª ÙÙ ÙÙÙØ³ Ø§ÙØ·ÙØ§Ø¨ Ø´Ø®ØµÙØ© ÙÙÙØ© ÙØ«Ù ØØ¨Ù Ø§ÙØ¨ÙØ¦Ø©.